2016
DOI: 10.1080/10245332.2015.1106815
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ASXL1 mutations in myelodysplastic syndromes and chronic myelomonocytic leukemia: A meta-analysis

Abstract: ASXL1 mutations were associated with poor prognosis in MDS, which may contribute to risk stratification and prognostic assessment in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 44 publications
2
25
1
1
Order By: Relevance
“…has also previously demonstrated that there were no significant correlations between SETBP1 mutations and age, and gender in CMML patients [ 11 ]. Our results show that the prognostic impact of SETBP1 mutations is similar to that of ASXL1 mutations, which is one of the strongest independent negative prognostic factor [ 13 , 20 ] in MDS and CMML patients (HR = 1.45, 95% CI (1.24–1.70)) [ 21 ].…”
Section: Discussionmentioning
confidence: 82%
“…has also previously demonstrated that there were no significant correlations between SETBP1 mutations and age, and gender in CMML patients [ 11 ]. Our results show that the prognostic impact of SETBP1 mutations is similar to that of ASXL1 mutations, which is one of the strongest independent negative prognostic factor [ 13 , 20 ] in MDS and CMML patients (HR = 1.45, 95% CI (1.24–1.70)) [ 21 ].…”
Section: Discussionmentioning
confidence: 82%
“…Mutations of ASXL1 have been reported in various types of leukemia 7, 8 . Although ASXL1 is considered to be a tumor suppressor, the molecular mechanism underlying tumor suppression is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…These findings add complexity to the known ASXL1 functions. In contrast to the positive role of ASXL1 in the cell cycle progression during early embryogenesis, ASXL1 has been speculated to be a potential tumor suppressor because of frequent mutations in various myeloid leukemia 7, 8 . Intriguingly, overexpression of EZH2 has been found in various types of human cancers, including prostate and breast cancer 35, 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency is slightly different between single groups. The highest percentage of mutated patients can be found in chronic myelomonocytic leukemia (CMML), followed by myelofibrosis, secondary AML, MDS and de novo AML, with frequencies of about 50%, 35%, 30%, 15% and 8%, respectively [92,93]. Acquired ASXL1 mutations are frequently frameshift and nonsense, around the Gly-rich domain (amino acids 642-685) on exon 12, and cause the expression of truncated ASXL1, with loss of the PHD domain, crucial for the regulation of key genes involved in stem-cell maintenance and myeloid differentiation (Table 2, Figure 2) [94].…”
Section: Asxl1 Mutationsmentioning
confidence: 99%